HARMONY: a pragmatic cluster randomised controlled trial of a culturally competent systems intervention to prevent and reduce domestic violence among migrant and refugee families in general practice: study protocol. Issue 7 (29th July 2021) - Taft, Angela; Young, Felicity; Hegarty, Kelsey; Yelland, Jane; Mazza, Danielle; Boyle, Douglas; Norman, Richard; Garcia-Moreno, Claudia; Nguyen, Cattram Duong; Li, Xia; Pokharel, Bijaya; Allen, Molly; et al.
Abstract : Introduction: Domestic violence and abuse (DVA) is prevalent, harmful and more dangerous among diaspora communities because of the difficulty accessing DVA services, language and migration issues. Consequently, migrant/refugee women are common among primary care populations, but evidence for culturally competent DVA primary care practice is negligible. This pragmatic cluster randomised controlled trial aims to increase DVA identification and referral (primary outcomes) threefold and safety planning (secondary outcome) among diverse women attending intervention vs comparison primary care clinics. Additionally, the study plans to improve recording of DVA, ethnicity, and conduct process and economic evaluations. Methods and analysis: Recruitment of ≤28 primary care clinics in Melbourne, Australia with high migrant/refugee communities. Eligible clinics need ≥1 South Asian general practitioner (GP) and one of two common software programmes to enable aggregated routine data extraction by GrHanite. Intervention staff undertake three DVA training sessions from a GP educator and bilingual DVA advocate/educator. Following training, clinic staff and DVA affected women 18+ will be supported for 12 months by the advocate/educator. Comparison clinics are trained in ethnicity and DVA data entry and offer routine DVA care. Data extraction of DV identification, safety planning and referral from routine GP data in both arms. Adjusted regression analysis by intention-to-treat by staff blinded to arm. Economic evaluation will estimate cost-effectiveness and cost–utility. Process evaluation interviews and analysis with primary care staff and women will be framed by Normalisation Process Theory to maximise understanding of sustainability. Harmony will be the first primary care trial to test a culturally competent model for the care of diverse women experiencing DVA. Ethics and dissemination: Ethical approval from La Trobe University Human Ethics Committee (HEC18413) and dissemination by policy briefs, journal articles and conference and community presentations. Trial registration number: ANZCTR- ACTRN12618001845224; Pre-results.